Involving the headteacher in the development of school-based health interventions: A mixed-methods outcome and process evaluation using the RE-AIM framework - Danielle Christian (PLOS ONE, 2020)
Although interventions delivered in school settings have the potential to improve children’s health and well-being, the implementation of effective interventions in schools presents challenges. Previous research suggests facilitating greater autonomy for schools to select interventions aligned to their needs could improve implementation and maintenance. The aim of this mixed-methods outcome and process evaluation was to explore whether involving headteachers in the developmental stages of health interventions influenced adoption, effectiveness (e.g. pupil fitness and physical activity, assessed quantitatively), implementation and maintenance (assessed quantitatively and qualitatively).Three UK primary schools were provided with a choice of five evidence-based physical activity interventions: Playground scrapstore, daily classroom refreshers, alternative afterschool clubs, parent and child afterschool activities and an ‘In the Zone’ playground intervention. To evaluate the impact of this autonomous approach, semi-structured interviews with headteachers (n = 3), teachers (n = 3), and a private coach, and focus groups with pupils aged 9–11 (n = 6, 31 pupils, 15 boys), were undertaken. This was alongside an outcome and process evaluation, guided by the RE-AIM framework. This study assessed the impacts on adoption, implementation and maintenance of the autonomous approach and the effect on physical activity (seven day accelerometry–GENEActiv) and aerobic fitness (20m shuttle run). All three schools adopted different intervention components; alternative afterschool clubs, parent and child afterschool activities and daily classroom refreshers. Headteachers welcomed greater autonomy in developing school-based interventions and appreciated the more collaborative approach. Mixed results were reported for the effectiveness, implementation and maintenance of the interventions adopted. Allowing pupils choice and promoting a positive school environment were key factors for enhancing engagement. Moreover, promoting inclusive physical activity projects with a consideration of existing curriculum pressures aided implementation. This mixed-methods study provides valuable insights about autonomous approaches to inform further development, implementation and maintenance for future interventions.